Early growth and symbiotic properties of three woody legumes grown on a sandy soil in southwestern Nigeria - Mulongoy, K.; Owoaje, B.T. (1992)
The early growth and symbiotic properties ofthree woody legumes, Cassia siamea, Gliricidia sepium and Leucaena leucocephala, were monitored on a farmer's field and in the screenhouse using the same soil. L. leucocephala and G.. septum nodulated freely and were heavily infected by native vesicular-arbuscular mycorrhizal fungi. Six months after planting, G. sepium had the highest dry-matter production, percentage of mycorrhizal infection, nodule number, dry weight and nitrogenase activity per plant in the treatment in which no nitrogen fertilizer had been applied. C. siamea did not nodulate and showed no nitrogenase activity. Inoculation ofL. leucocephala w\thRhizobium strain TAL 1 145 increased nitrogen fixation, dry-matter production and nitrogen yield. G. sepium and inoculated L. leucocephala plants had values of relative effectiveness in nitrogen fixation close to 100%, indicating effective symbioses with rhizobia. Phosphorus application increased the dry-matter production of all species, especially when combined with nitrogen fertilizer. All plant parameters studied had generally higher values in the field than in the screenhouse. The ranking of species on the basis of the parameters studied was the same for plants grown in field and in screenhouse, particularly in the treatment involving no nitrogen fertilizer.